المعرفة السوقية والاستراتيجيات التنافسية في مؤسسات الأعمال الجزائرية دراسة تطبيقية على مؤسسة مناجم الفوسفات - راهم, فريد; قاطر, فارس (جامعة الوادي - University of Eloued, 2017)
This Study Aimed at Clarifying The Role Of Market Knowledge In Determining The Competitive Strategies Of The Algerian Economic Establishment, Through The Phosphate Mines Company, And To Clarify The Application Of The Company Under Study Market Knowledge With Its Dimensions In Adopting The Strategy Of Cost Leadership Or Fixity And Stability Or Focus, Or Development And Improvement, Or Deflation Strategy. This Is Through The SWOT Analysis To Choose The Appropriate Strategy .The Study Found That The Company Under Study Used The Market Knowledge With Its Dimensions, To Determine The Appropriate Competitive Strategy, And Therefore The Strategy Used Is The Strategy Of Control At Cost, But Did Not Achieve Any Competitive Position, Especially Compared To Its Neighbors Morocco And Tunisia
Market knowledge and competitive strategies in Algerian business Applied Study on Phosphate Mines company
مقال
Keywords: المعرفة السوقية، الاستراتيجيات التنافسية، مؤسسات الاعمال، تحليل SWOT.; Market Knowledge, Competitive Strategies, Businesses, SWOT Analysis